Characterisation of mutations and molecular studies of type 2 von Willebrand disease - Ahmad, Firdos; Jan, Rifat; Kannan, Meganathan; Obser, Tobias; Hassan, Md Imtaiyaz; Oyen, Florian; Budde, Ulrich; Saxena, Renu; Schneppenheim, Reinhard (Thrombosis and Haemostasis, 2013)
Type 2 von Willebrand disease (VWD) is characterised by qualitative defects in von Willebrand factor (VWF). Exon 28 of the VWF gene is known to be a hot spot for type 2 VWD mutations. The goal of this study was to characterise the mutations in VWF exon 28 and understand the molecular basis of phenotypes through in vitro and in silico studies. Mutation screening was performed in 56 type 2 VWD patients through direct sequencing. Expression vectors for five mutations were transiently expressed in 293-EBNA cells to understand the mutations pathology. Furthermore, in silico structure analysis was performed for 13 missense mutations.A total of 16 including eight novel mutations were detected in 23 (41%) patients. Of these, 15 were missense (including seven V1439M, A1464P, M1495L, I1509V, R1527Q, N1635I and A1647D novel ones) and one was a novel gene conversion. Expression studies and characterisation of recombinant VWF suggested the loss of VWF function for mutants P1266Q, V1439M and N1635I and gain of function for mutant R1308C. No apparent defect was seen in mutant N1231S. In silico structure analysis suggested the probable gain or loss of hydrogen/van der Waals interactions in 10 mutant proteins. In conclusion, type 2A mutations and gene conversion were found to be a common cause of type 2 VWD. Expression studies suggest the mutations N1635I for type 2A(II), P1266Q and V1439M for type 2M, R1308C for type 2B VWD and N1231S as a non-causative variant. Moreover, in silico studies of the mutants show the probable cause of respective phenotypes.
Keywords: Type 2 VWD mutation; gene conversion; phenotype genotype; in vitro expression; molecular modelling